The Enigma of Faith - Thierry, William of Saint (Monastic Studies Series, 2010)
William of Saint Thierry left all things in his search for God. He left his home in Liège (modern Belgium) to study in France. He left the schools to enter Benedictine monastic life at Rheims. And late in life he left the Benedictines to enter the most austere, recently founded Cistercian abbey of Signy in the Ardennes forest. What he did not leave was his keen intellect and his vehement love of Truth